Walford's guide to reference material : volume 1 science and technology - Walford, A J. (Library Association, London, 1999)
The purpose of Walford has been to identify and evaluate the widest possible range of reference materials. In addition to the expected bibliographies, indexes, dictionaries, encyclopaedias and directories, a number of important textbooks and manuals of general practice are included. While the majority of items are reference books, Walford is a guide to reference material. Thus periodical articles, microforms, online and CD-ROM sources are all represented and there is an index of online and database services.
Includes index
usc 08/11/2021
Ref.
Keywords: Reference books; Philosophy; Religion; Social sciences